The European Union’s Strategic Adaptations to Hybrid Conflicts and the Influence of External Actors - Marsili, M. (Studia Administracji i Bezpieczeństwa [Public Administration and Security Studies], 2025)
This article explores how the European Union has strategically adapted to the growing threat of hybrid conflicts, using the war in Ukraine as a pivotal case study. It examines institutional reforms in EU crisis governance, enhanced coordination with NATO, and evolving strategies in cyber defense, energy resilience, and disinformation countermeasures. The article also analyzes how major global actors—including Russia, the United States, and China—shape the EU’s security and policy landscape. Applying institutional and network resilience theory, the article assesses the Union’s ongoing transformation toward greater strategic autonomy and crisis preparedness in a destabilized international order.